2020
DOI: 10.1111/lam.13260
|View full text |Cite
|
Sign up to set email alerts
|

Loop mediated isothermal amplification assay for detection of Trichomonas vaginalis in vaginal swabs among symptomatic women from North India

Abstract: Significance and Impact of the Study: Trichomonas vaginalis is a common sexually transmitted pathogen associated with considerable morbidity and risk of complications. Due to the limitations of traditional diagnostic modalities, three molecular assays were compared: conventional polymerase chain reaction (PCR), Xpert TV assay, and loop mediated isothermal amplification (LAMP) assay for detecting T. vaginalis in symptomatic females. All tests had a sensitivity of 100% and the inter-rater reliability was excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The second swab (cervical or cervicovaginal) was used to inoculate onto chocolate agar and it was then squeezed thoroughly into a falcon tube containing molecular grade water for DNA extraction. The DNA was extracted using Chelex® (Sigma Aldrich, MO, USA) and amplified for detecting the presence of TV, Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) using polymerase chain reactions (PCRs), as described earlier[ 10 11 ] [ Supplementary File ]. The chocolate agar and blood agar plates were incubated in a CO 2 incubator (Binder, GmbH Germany) at 37°C for at least 72 h, the plates were examined for the presence of any visible growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second swab (cervical or cervicovaginal) was used to inoculate onto chocolate agar and it was then squeezed thoroughly into a falcon tube containing molecular grade water for DNA extraction. The DNA was extracted using Chelex® (Sigma Aldrich, MO, USA) and amplified for detecting the presence of TV, Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) using polymerase chain reactions (PCRs), as described earlier[ 10 11 ] [ Supplementary File ]. The chocolate agar and blood agar plates were incubated in a CO 2 incubator (Binder, GmbH Germany) at 37°C for at least 72 h, the plates were examined for the presence of any visible growth.…”
Section: Methodsmentioning
confidence: 99%
“…and Ureaplasma urealyticum . The urine specimens obtained were subjected only to PCR, as described earlier[ 10 11 ] [ Supplementary File ].…”
Section: Methodsmentioning
confidence: 99%
“…The second swab was used to put up NG and CT PCR using three conventional PCRs, as described earlier. [ 5 6 ] The swab was thoroughly squeezed in molecular grade water for DNA extraction. DNA was extracted using Chelex® (Sigma Aldrich, MO, USA) and amplified.…”
Section: Methodsmentioning
confidence: 99%
“…And as far as we know, our work has been the first to simultaneously detect T. vaginalis and different types of HPV with LAMP and microfluidic-chip technology, though several studies have reported detection of T. vaginalis or HPV with LAMP or combined with microfluidic chips. 18,34 There have been many studies employing microfluidic systems with LAMP for nucleic acid detection. 19,35,36 We compared our microfluidic-chip-based system with previous reported works, in particular to those targeting related pathogens using LAMP (Table S3 †).…”
Section: Detection Performance Of the Microfluidic-chip Analysis Systemmentioning
confidence: 99%